Kihito, a Traditional Japanese Kampo Medicine, Improves Cognitive Function in Alzheimer's Disease Patients. (14th May 2019) - Watari, Hidetoshi; Shimada, Yutaka; Matsui, Mie; Tohda, Chihiro
Abstract : Background and Aims . We previously reported that the administration of traditional Japanese medicines, kihito (Gui-Pi-Tang in Chinese) and kamikihito (Jia-Wei-Gui-Pi-Tang in Chinese), to Alzheimer's disease (AD) model mice improved memory impairment. There are a few reports that show kihito and kamikihito have a beneficial effect on the cognitive function of AD patients in clinical studies. However, these studies are not comparative and are retrospective studies; thus, more evidence is needed. Therefore, we conducted an open-label, crossover designed clinical trial to investigate the effect of kihito on cognitive function of AD patients. Methods . The inclusion criteria for eligible patients were as follows: (1) imaging diagnosis (magnetic resonance imaging and single-photon emission computed tomography) of AD, (2) a treatment regimen including acetylcholinesterase inhibitors (ChEIs), and (3) a Mini-Mental State Examination (MMSE) score ≥15. The exclusion criteria were as follows: (1) change in ChEI dosage, (2) memantine usage, and (3) MMSE score < 15. To prevent bias in age and baseline cognitive function, patients were divided into two groups: the first group received 2.5 g of kihito extract 3 times/day during the first half of the study (weeks 0-16) and the second group received the same dose of kihito during the second half of the study (weeks 17-32). ChEI dosage did not change during the study period. Patients underwent a cognitive function test during weeks 0, 16, and 32. Cognitive function was evaluated by Japanese versions of the Mini-Mental State Examination (MMSE-J) and the Repeatable Battery for the Assessment of Neuropsychological Status (RBANS-J) test. Results . Ten patients completed the clinical trial (4 males, 6 females, average age 71.7 years). MMSE-J scores significantly increased during the kihito intake period. RBANS-J test scores had a slight improvement during the kihito intake period compared with the ChEI alone treatment period, but no significant changes were observed. Conclusion . Kihito improves cognitive function in AD patients.